Hyperthermia-triggered release of hypoxic cell radiosensitizers from temperature-sensitive liposomes improves radiotherapy efficacy in vitro. (12th April 2019) - Sadeghi, Negar; Kok, Robbert Jan; Bos, Clemens; Zandvliet, Maurice; Geerts, Willie J C; Storm, Gert; Moonen, Chrit T W; Lammers, Twan; Deckers, Roel
Abstract: Hypoxia is a characteristic feature of solid tumors and an important cause of resistance to radiotherapy. Hypoxic cell radiosensitizers have been shown to increase radiotherapy efficacy, but dose-limiting side effects prevent their widespread use in the clinic. We propose the encapsulation of hypoxic cell radiosensitizers in temperature-sensitive liposomes (TSL) to target the radiosensitizers specifically to tumors and to avoid unwanted accumulation in healthy tissues. The main objective of the present study is to develop and characterize TSL loaded with the radiosensitizer pimonidazole (PMZ) and to evaluate the in vitro efficacy of free PMZ and PMZ encapsulated in TSL in combination with hyperthermia and radiotherapy. PMZ was actively loaded into TSL at different drug/lipid ratios, and the physicochemical characteristics and the stability of the resulting TSL–PMZ were evaluated. PMZ release was determined at 37 °C and 42 °C in HEPES buffer saline and fetal bovine serum. The concentration-dependent radiosensitizing effect of PMZ was investigated by exposing FaDu cells to different PMZ concentrations under hypoxic conditions followed by exposure to ionizing irradiation. The efficacy of TSL–PMZ in combination with hyperthermia and radiotherapy was determined in vitro, assessing cell survival and DNA damage by means of the clonogenic assay and histone H2AX phosphorylation, respectively. All TSL–PMZ formulations showed high encapsulation efficiencies and were stable for 30 d upon storage at 4 °C and 20 °C. Fast PMZ release was observed at 42 °C, regardless of the drug/lipid ratio. Increasing the PMZ concentration significantly enhanced the effect of ionizing irradiation. Pre-heated TSL–PMZ in combination with radiotherapy caused a 14.3-fold increase in cell death as compared to radiotherapy treatment alone. In conclusion, our results indicate that TSL–PMZ in combination with hyperthermia can assist in improving the efficacy of radiotherapy under hypoxic conditions.